2021
DOI: 10.3390/molecules26164733
|View full text |Cite
|
Sign up to set email alerts
|

Berberine, A Phytoalkaloid, Inhibits Inflammatory Response Induced by LPS through NF-Kappaβ Pathway: Possible Involvement of the IKKα

Abstract: Berberine (BBR), a plant alkaloid, is known for its therapeutic properties of anticancer, cardioprotective, antidiabetic, hypolipidemic, neuroprotective, and hepatoprotective activities. The present study was to determine the molecular mechanism of BBR’s pharmacological activity in human monocytic (THP-1) cells induced by arachidonic acid (AA) or lipopolysaccharide (LPS). The effect of BBR on AA/LPS activated proinflammatory markers including TNF-α, MCP-1, IL-8 and COX-2 was measured by ELISA or quantitative r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
10
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 16 publications
(10 citation statements)
references
References 48 publications
(56 reference statements)
0
10
0
Order By: Relevance
“…Not surprisingly, of the 175 small molecule anti-tumor agents approved between the 1940s to 2014, almost 50% of them were derived directly from various natural products [ 28 ]. As a class of natural isoquinoline alkaloids, berberine has been shown to possess extensive pharmacological activities, such as anti-inflammatory, antioxidant, and anti-diabetes effects [ 15 , 29 , 30 ]. In addition, berberine has been of interest for years due to its anti-tumor activity of interfering with a variety of characteristics of tumorigenesis and tumor development.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Not surprisingly, of the 175 small molecule anti-tumor agents approved between the 1940s to 2014, almost 50% of them were derived directly from various natural products [ 28 ]. As a class of natural isoquinoline alkaloids, berberine has been shown to possess extensive pharmacological activities, such as anti-inflammatory, antioxidant, and anti-diabetes effects [ 15 , 29 , 30 ]. In addition, berberine has been of interest for years due to its anti-tumor activity of interfering with a variety of characteristics of tumorigenesis and tumor development.…”
Section: Discussionmentioning
confidence: 99%
“…Berberine, a major isoquinoline alkaloid constituent of many medicinal herbs, such as Coptidis rhizome and Berberis vulgaris , has shown great promise as an anti-cancer agent [ 15 ]. Studies have reported several important molecular mechanisms responsible for the anti-cancer effect of berberine.…”
Section: Introductionmentioning
confidence: 99%
“…Berberine has been demonstrated to have comparable effects in the treatment of T2DM with antidiabetic drugs like metformin that display multiple targets and pathways. For patients with T2DM, the main function of berberine is as a SIRT1 or AMPK agonist to mimic energy restriction [ 75 77 ] and to target on NF- κ B [ 78 ] to improve insulin resistance and inflammation as well as to alleviate the activation of ox-LDL-induced macrophages [ 79 ]. In addition, berberine stabilizes LDL receptor mRNA to increase the clearance rate of plasma LDL [ 80 ].…”
Section: Discussionmentioning
confidence: 99%
“…Studies involving animal models of LPS-induced neuroinflammation are utilized to assess in vivo activity of compounds tested for this purpose for the first time. Both of these methods may be also used with the aim of explaining the exact mechanism of action and specific effects of substances with already established neuroprotective activity [ 41 , 111 , 112 ]. The most important factors limiting the therapeutic use of these substances are often their low bioavailability in humans and not sufficient level of BBB crossing.…”
Section: Future Outlookmentioning
confidence: 99%